2009
DOI: 10.1128/ec.00002-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Candida albicans Cap1p Regulon

Abstract: Cap1p, a transcription factor of the basic region leucine zipper family, regulates the oxidative stress response (OSR) in Candida albicans. Alteration of its C-terminal cysteine-rich domain (CRD) results in Cap1p nuclear retention and transcriptional activation. To better understand the function of Cap1p in C. albicans, we used genome-wide location profiling (chromatin immunoprecipitation-on-chip) to identify its transcriptional targets in vivo. A triple-hemagglutinin (HA 3 ) epitope was introduced at the C te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(141 citation statements)
references
References 72 publications
5
135
1
Order By: Relevance
“…Western blot analyses of strains grown under P MET3 -inducing conditions showed that both Sfl1p-HA 3 and Sfl2p-HA 3 fusion proteins were expressed ( Figure 1B, lanes 4 and 6). As an additional control for signal specificity, immunoblotting of total extracts from a C. albicans strain expressing the Cap1p-HA 3 fusion ( Figure 1, lane 2) or the corresponding empty-vector negative control ( Figure 1, lane 1) was used [43].…”
Section: Epitope-tagging Of Sfl1p and Sfl2pmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analyses of strains grown under P MET3 -inducing conditions showed that both Sfl1p-HA 3 and Sfl2p-HA 3 fusion proteins were expressed ( Figure 1B, lanes 4 and 6). As an additional control for signal specificity, immunoblotting of total extracts from a C. albicans strain expressing the Cap1p-HA 3 fusion ( Figure 1, lane 2) or the corresponding empty-vector negative control ( Figure 1, lane 1) was used [43].…”
Section: Epitope-tagging Of Sfl1p and Sfl2pmentioning
confidence: 99%
“…(B) Western blot analysis of homozygous sfl1 or sfl2 mutants (sfl1D/sfl1D or sfl2D/sfl2D) expressing HA 3 -tagged versions of the SFL1 or SFL2 genes, respectively (SFL1-HA 3 or SFL2-HA 3 ) together with the corresponding empty vector controls (Vector). The SGY243 strain expressing the CAP1-HA 3 (CAP1-HA 3 ) or carrying the empty vector (Vector) were used as a positive control [43]. Strains were grown overnight in SD medium (P MET3 -inducing conditions) and total protein extracts were prepared then subjected to SDS-PAGE.…”
Section: Author Summarymentioning
confidence: 99%
“…They are respectively named Cgap1p and Cap1p and are also involved in the response to oxidative stress (Chen et al, 2007;Lelandais et al, 2008;Znaidi et al, 2009). Infections caused by fungal pathogens have become major life-threatening diseases, especially in patients with defects in their immune system.…”
Section: Yap Proteins and The Response To Oxidative Stressmentioning
confidence: 99%
“…These sets of genes are referred to as AP-1 transcriptional modules (TMs). In each yeast species, benomyl is known to activate an oxidative stress, for which the genomic response of the cell is primarily dependant on the TFs Yap1p (Lucau-Danila et al, 2005), Cgap1p and Cap1p (Znaidi et al, 2009). To summarize, our strategy consisted in considering three different layers of information based on the analysis of genome-wide datasets.…”
Section: General Principlementioning
confidence: 99%
See 1 more Smart Citation